Factores que limitan la aplicación del reglamento de ley n°29783 de seguridad y salud en el trabajo, para la satisfacción laboral de los trabajadores de las diferentes contratas y los trabajadores del proyecto especial huallaga central y bajo mayo, del distrito de tarapoto, región san martín, año 2014 - Calderón Sare, Erika Nereyda (2015)
The importance of promoting a culture of prevention in health and safety progressively ensuring a safe and healthy workplace for all workers in the country, makes us aware of this situation and contribute to the practice of a job safe and healthy, and that the shortfall in health and safety at work requires a firm commitment by government authorities as well as the participation and collaboration of employers and workers in all sectors and society as a set. That is why we have conducted a research to know, what are the factors that limit the proper application of Regulation Act No. 29783 Safety and Health at Work are; with the aim of preventing accidents, occupational diseases and reduce the damage that could be caused to the health of workers and employees. The results of this study allowed us to identify some of the factors that limit the application of Regulation No. 29783 Law in different works, which is required for acceptance and practice to avoid accidents and many of them irreparable. We begin to research knowing the Reality Problems identifying the research problem. In Chapter I, know the general characteristics of workers PEHCBM; Chapter II, is based on the knowledge of the Rules of Law No. 29783 Safety and Health at Work, likewise, Chapter III, will discuss the proper use of PPE's, for employers to then see in chapter IV, on the vulnerability of workers, how these for fear of dismissal do not enforce their rights. Recalling provided: Working Safely ensuring their health ... is a condition of employment.